The role of green marketing in addressing environmental and economic challenges in Jordan - Hussam Ali; Hanadi A. Salhab (Environmental Economics)
This study investigates the role of green marketing in addressing Jordan’s environmental and economic challenges, focusing on barriers and drivers of adoption. Using a quantitative research approach, data were collected from 504 respondents (67.5% were customers and 32.5% were SME owners) and analyzed through partial least squares structural equation modeling to evaluate the relationships between socio-economic factors, financial incentives, and infrastructural challenges. The results reveal that financial incentives significantly drive the adoption of renewable energy (coefficient: 0.85, p = 0.010) and sustainable agriculture (coefficient: 0.80, p = 0.014). Stakeholder engagement is high, with customer awareness scoring a mean of 4.1 (standard deviation: 0.5) and environmental sustainability at 4.2 (standard deviation: 0.5). Key barriers include infrastructural limitations (mean: 3.7, standard deviation: 0.8) and socio-economic disparities (mean: 3.8, standard deviation: 0.7), restricting access to eco-friendly products. Model fit indices, including a standardized root mean square residual of 0.054 and a normed fit index of 0.92, confirm the robustness of the framework. The findings suggest that overcoming these barriers requires targeted financial support, infrastructure investment, and inclusive policies to scale green marketing effectively. This paper provides actionable insights into advancing sustainable practices in Jordan, offering valuable strategies for resource-constrained economies worldwide.